Towards an improved provision of socialized housing an assessment of the implementation of the community mortgage program of the local government units (LGUs) - Zapanta, Rowena T.; David Leonides T. Yap. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
The rapid population growth prevalent in the urban areas results in greater demand for basic social services, including housing. As the demand increases, the government has to find better ways to sustain the housing program in the country.The provision of housing programs have undergone an evolution from a centralized approach, where the national government is vested with the authority to provide for the housing needs of the country, to a highly decentralized approach where local government units (LGUs) and the private sector were given an avenue to participate in addressing the housing needs. In the decentralized approach, the LGU serves as the bridge between the key shelter agencies of the National Government and the communities. LGUs also play a major role as a facilitator to ensure the sustainability of the housing services to the communities. Today, the decentralized approach in the housing provision is practiced by LGUs through various community-based housing programs. Among these community-based housing programs, the Community Mortgage Program (CMP) is considered to be most popular because of its coast effectiveness and wider beneficiary reach. The study theorizes that better provision of socialized housing is dependent on the effectiveness of community-based housing programs at the local level. The study focused on CMP and assessed the implementation of the CMP at the LGU level through the experiences of the City of Antipolo : how the LGU was able to utilize its authority levers to address the challenges they have encountered in implementing the CMP. It is the hope of the author that issues and concerns of the LGU and how these were addressed by the City of Antipolo may provide insights to sustain the housing program through the CMP.
Thesis (M.S in Regional and Development Planning)--University of the Philippines Diliman
Keywords: Housing -- Philippines -- Finance; Housing policy -- Philippines; Public housing -- Philippines -- Finance